A survival analysis of songs on digital music platform. Issue 6 (September 2018) - Im, Hyunsuk; Song, Haeyeop; Jung, Jaemin
Highlights: Being the title track is the most critical factor for songs' survival on the download and streaming charts. Major labels are no longer superior to minor labels in survival of streaming services. The superstar is positive to the survival on the streaming chart. The superstar is effective only in the interaction with being title track on the download. Piracy shows a negative influence on the survival of songs for both download and streaming service. Abstract: This study explores and compares what factors are critical for music to succeed in download and streaming services. The weekly top 100 songs listed on the Korean music ranking charts for three years were used as the sample, and the factors affecting success on the download and streaming ranking charts were examined using the survival analysis. The results indicate that being the title track is the most critical factor for songs' survival on the charts for both services. While songs released by major labels survived longer on the download chart, major labels are no longer superior to minor labels in streaming services. The results also indicate the impact of the superstar was positive to the survival on the streaming chart, but it was effective only in the interaction with being title track on the download. As expected, piracy showed a negative influence on the survival of songs for both download and streaming service. Theoretical and practical implications for the digital music industry were suggested.